Survival rate of bat bugs (Cimex pipistrelli, Heteroptera) under different microclimatic conditions - Bartonicka, Tomas (Parasitology research, 2010)
Survival of facultative ectoparasites, e.g. bed bugs (Cimex spp.), is more intensely affected by climatic factors, namely temperature, than that of permanent ectoparasites. The ontogenetic time of the bat bug (Cimex pipistrelli) in bat roosts is limited by different survival rates under different temperatures in particular nymphal stages. This limitation could affect bug densities and cause asynchrony between the ectoparasite and bat reproductive cycle. Therefore, bug survival under different temperatures was tested in the laboratory. Survival success was evaluated by three types of survival analyses: Kaplan-Meier estimation, the Cox proportional hazards model and Weibull parametric regression. The bugs survived for only a few hours at 45 degrees C; however, such a high temperature was never found in natural roosts. Different survival probability among different ontogenetic stages was found at the temperatures of 5-35 degrees C, and it was the highest in adult females and nymphs of fourth and fifth instar. Early instars first to third were found to be the most sensitive with the highest mortality of all stages studied and having their best survival at 5 degrees C. The hazard rate ratio of Weibull regression shows the low daily failure rate of 2.23-4.34% within the span of 5-35 degrees C. C. pipistrelli had the shorter life cycle and the better survival at higher temperature (35 degrees C) than C. lectularius. The ability of the former to survive high temperatures could be the consequence of its long-term coexistence with bats preferring crevice-like roosts or attics which become overheated during the summer months.
Keywords: Bedbugs; štěnice; Survival Analysis; analýza přežití; Temperature; teplota; Animals; zvířata